Analisis Tata Letak Fasilitas Toko Retail Red Mart Kota Bogor Dengan Metode ARC dan TCR - Azrina Qisthina Zamila; Amalia Putri Azahrah; Naufal Aditya; Ledia W.A. Sitanggang (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Layout is a procedure for arranging facilities to support the smooth running of operational processes within them. This arrangement is by trying to utilize the area (space) to place material storage (storage) both temporary and permanent, smooth the movement of material, worker personnel and so on. The focus of this research is to analyze the layout of Red Mart retail store facilities. The analysis methods used are ARC and TCR. The results of this facility layout analysis are in accordance with the ARC and TCR calculations. Based on the TCR calculation results, it shows that the product shelf has the highest value, namely 103, indicating that the product shelf must be built first and placed in a strategic location. Other facilities such as cashiers, refrigerators, toilets and warehouses also have quite high TCR values, indicating the importance of these facilities in layout planning.